Understanding Civic Crowdfunding as a Mechanism for Leveraging Civic Engagement and Urban Innovation - Bastiaan Baccarne; Tom Evens; Lieven De Marez (Technology Innovation Management Review, 2020)
This article studies the emergence of government-initiated civic crowdfunding platforms. Such platforms can be considered as governmental responses for bottom-up peer-to-peer support mechanisms related to urban innovation, which also allows top-down governance and governmental support systems for civic entrepreneurship. To better understand the implications of these innovative ICT-enabled interaction interfaces for collective urban innovation, this study investigates participation inequalities from the perspective of campaign instigators, using in-depth interviews (N=28), and from the perspective of the citizen-funder, using a survey (N=265). The analysis shows that urban crowdfunding practices mainly contribute to higher-level development of collective identities with increased neighborhood capacities. Although participation in such ICT-enabled interaction interfaces could reinforce digital inequalities and existing power balances, this research shows a more nuanced perspective, in which online and offline practices intertwine. Furthermore, while civic crowdfunding campaigns are driven by a traditional 'participation elite', the deliberation process on development projects involves new publics that are not typically engaged in civic activities. Hence, civic crowdfunding formulates a new mode of civic engagement in which institutional involvement acts as a trust broker between civic funders and civic entrepreneurs, as well as adding legitimacy to innovation processes in the public sphere.